Building Strategic Planning Models Based on Digital Technology in the Sharia Capital Market - BASROWI, Basrowi; UTAMI, Pertiwi (Journal of Advanced Research in Law and Economics, 2020)
Digital technology is able to give a new face to the development of the capital market industry in Indonesia. Licensing process, wider reach and ease in transactions (financial technology) become faster, more efficient, cheaper, and transparent. However, the development of digital or scripless systems is still constrained by various factors. The purpose of this study is to try to dig deeper into the basic concepts of digital planning for issuers in the list of Islamic securities. A development model based on the results of the literature review is expected to contribute to the acceleration of digital technology in the capital market. The results of the study suggest that it is important for digital planning so that organizations have planning standards with special characteristics to create a 'positioning' that is in accordance with Islamic principles. The novelty in this research is that social cognitive theory and technology adoption can also be applied to sharia-based digital planners in the capital market. Sharia-based digital technology will have a positive impact on the empowerment of issuers, prospective issuers, and investors in the list of sharia securities.